5
$\begingroup$

Let $f(z)$ be an entire function of finite order of the form $$f(z)=\sum_{n=0}^\infty a_nz^{k_n}$$ where $a_n\neq0$ for all $n$ and $(k_n)_{n\geq0}$ is an increasing sequence of integers satisfying $$\limsup_n\;(k_{n+1}-k_n)=\infty.$$ Show that $f(z)$ has infinitely many zeros.

I know that if $f(z)$ has only finitely many zeros then by Hadamard's theorem $f(z)$ is of the form $P(z)e^{Q(z)}$ for some polynomials $P$ and $Q$, so a possible approach is to show that for such functions the condition $\limsup_n\;(k_{n+1}-k_n)=\infty$ is not possible, but I gave up after some time. Another possible way may be trying to prove that $f(z)$ has non-integer order, since in such a case it follows easily that $f(z)$ cannot have finitely many zeros. Any ideas?

$\endgroup$
  • $\begingroup$ An intuitive argument, that I admittedly don't really know how to formalize in an acceptable manner, is to see that a function of the form $P(z)e^{Q(z)}$ depends on a finite number of parameters. However, if the set $k_n$ satisfies the given condition, then one would have to make an infinite number of derivatives at z=0 equal to zero, which would imply an infinite number of equations on finite parameters... doesnt imply a solution doesn't exist but at least hints at it... $\endgroup$ – DinosaurEgg May 22 at 11:01
3
$\begingroup$

As you said, if $f$ has only finitely many zeros, it is of the form $f(z) = P(z) e^{Q(z)}$ with polynomials $P(z) = p_m z^m + \ldots + p_0$ and $Q(z) = q_n z^n + \ldots + q_0$. (All leading coefficients are assumed to be non-zero.) Then $P(z) f'(z) = R(z) f(z)$ with $R(z) = P'(z) + P(z)Q'(z) = r_N z^N + \ldots + r_0$, where $N=m+n-1 \ge m$. Writing this out in coefficients, you get $$ (p_m z^m + \ldots + p_0) \sum_{j=0}^\infty k_j a_j z^{k_j-1} = (r_N z^N + \ldots + r_0) \sum_{j=0}^\infty a_j z^{k_j} = \sum_{k=0}^\infty b_k z^k $$ Now pick some $j$ such that $k_{j+1} - k_j > N+2$ and consider the largest $k \in \{ k_j, k_j +1 , \ldots, k_{j+1}-2\}$ such that $b_k \ne 0$. Multiplying out terms we have $k = m+k_j-1 = N+k_j$, which implies that $N = m-1$, contradicting $N \ge m$.

$\endgroup$
  • $\begingroup$ Thanks for your answer, but am I missing something or you've written $Rf'=Qf$ instead of $Pf'=Rf$ in the middle equation? $\endgroup$ – user246336 May 23 at 8:57
  • $\begingroup$ @user246336: Oops, yes, I'll fix that later, thanks for catching my mistake. However, the main argument still works in basically the same way. $\endgroup$ – Lukas Geyer May 23 at 15:35
  • $\begingroup$ @user246336: Actually, with this correction, the proof is even simpler than before. $\endgroup$ – Lukas Geyer May 23 at 20:18

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.